Selective binding of imidazolium cations in building multi-component layers - Ling, I.; Alias, Y.; Sobolev, A.N.; Byrne, L.T.; Raston, C.L. (Wiley-Blackwell, 2010)
Addition of 1-alky1-3-methyl-imidazolium (C(n)-mim) cations 3-5 to a mixture of his-phosphonium cation 2 and sodium p-sulfonatocalix[4]larene (I) in the presence of lanthanide ions results in the selective binding of an imidazolium cation into the cavity of the calixarene. The result is a multi-layered solid material with an inherently flexible interplay of the components. Incorporating ethyl-, n-butyl- or n-hexyl-mim cations into the multi-layers results in significant perturbation of the structure, the most striking effect is the tilting of the plane of the bowl-shaped calixarene relative to the plane of the multi-layer, with tilt angles of 7.2, 28.9 and 65.5 degrees, respectively. The lanthanide ions facilitate complexation. but are not incorporated into the structures and, in all cases, the calixarene takes on a 5 charge, with one of the lower-rim phenolic groups deprotonated. ROESY NMR experiments and other (1)H NMR spectroscopy studies establish the formation of 1:1 supermolecules of C(n)-mim and calixarene. regardless of the ratio of the two components, and indicate that the supermolecules undergo rapid exchange on the NMR spectroscopy timescale.